Pharmacognostical study of some species of tradescantia family commelinaceae cultivated in Egypt - Aya Mohamed Faisal Mohamed; Ibrahim Ibrahim Mahmoud; Manal Mahmoud Sabry; Seham Salah Eldin Elhawary (Cairo : Aya Mohamed Faisal Mohamed, 2019)
A preliminary phytochemical screening of the aerial parts of T. pallida (Rose) D.R.Hunt, T. zebrina Heynh ex.Bosse and T. spathacea Swartz. (Commelinaceae) cultivating in Egypt was carried out. Lipoidal contents was investigated in the petroleum ether extractive of T. pallida (Rose) D.R.Hunt. The phytochemical investigation of the flavonoidal and phenolic compounds using HPLC of the three species indicated that T. zebrina Heynh ex. Bosse possessed the highest percentage of flavonoid and phenolic content where Kamp3, (2-p-comaroyl) glucoside was the most abundant compound (2740 mg/100g). Analysis of the secondary metabolites of the three Tradescantia species using HPLC-PDA-MS/MS led to the identification of 27 phenolic compounds. The phytochemical investigation of T. pallida (Rose) D.R.Hunt led to the isolation of 1 steroidal compound. Ý-sitosterol compound was isolated from the petroleum ether extractive. In addition to the separation and identification of seven phenolic compounds from the n-butanol fraction by using LC-ESI-MS/MS (trans-cinnamic acid, caffeic-O-pentoside, p-coumaroyl-O-pentoside, quercetin, syringic-O-hexoside, naringenin and apigenin
Thesis (M.Sc.) - Cairo University - Faculty of Pharmacy - Department of Pharmacognosy
Issued also as CD
Keywords: HPLC; PDA; Tradescantia